β(2)‐adrenergic regulation of stress hyperglycemia following hemorrhage in the obese Zucker rat - Clemmer, John S. (Physiol Rep, 2014)
Stress hyperglycemia following trauma has been shown to potentiate morbidity and mortality. Glucose control in obese patients can be challenging due to insulin resistance. Thus, understanding the mechanisms for glucose generation following hemorrhage may provide important insights into alternative options for glycemic control in obesity. Obesity is characterized by elevated glycogen and increased hepatic β(2)‐adrenergic activity, which play major roles in glucose production after hemorrhage. We hypothesized that, in obesity, hepatic glycogenolysis is enhanced during stress hyperglycemia due to increased hepatic β(2)‐adrenoceptor activation. Hemorrhage was performed in conscious lean Zucker (LZ) and obese Zucker rats (OZ) by withdrawing 35% total blood volume over 10 min. Liver glycogen content and plasma levels of glucose, insulin, and glucagon were measured before and 1 h after hemorrhage. The hyperglycemic response was greater in OZ as compared to LZ, but glycogen content was similarly reduced in both groups. Subsequently, OZ had a greater fall in insulin compared to LZ. Glucagon levels were significantly increased 1 h after hemorrhage in LZ but not in OZ. To test the direct adrenergic effects on the liver after hemorrhage, we treated animals before hemorrhage with a selective β(2)‐adrenoceptor antagonist, ICI‐118,551 (ICI; 2 mg/kg/h, i.v.). After hemorrhage, ICI significantly reduced hyperglycemia in both LZ and OZ, independent of hormonal changes, but there was a significantly decreased hepatic glycogenolysis in OZ. These results suggest that the hemorrhage‐induced hepatic glycogenolysis is likely glucagon‐dependent in LZ, whereas the β(2)‐adrenoceptor plays a greater role in OZ.